#Men's Grooming Content in the Denim Discord Community "Darahku Biru" - Renada Ardio Praba Swara; Jandy Edipson Luik; Daniel Budiana (Journal of Content and Engagement, 2025)
Men's Grooming is men's grooming, which is a behavior of grooming and grooming carried out by men. The aim of this research is to find out how many men's grooming actions occur through discussions that occur in the media discord of Darahku Biru denim community. By taking data from 5 discord channels in Darahku Biru denim community discord as a place to collect data, namely the Jeans-and-Denim channel, Apparel channel, Leather-footwear channel, Localbrand channel, and Men's-grooming channel which is limited from April 1 2024 to April 30 2024 with a total of 96 samples. This research uses a quantitative content analysis method. The results of this research show that of the total chats on 5 channels, namely 876, there are 348 chats that discuss men's grooming content. The main indicator of body unity, the trousers indicator, is the one most often discussed. Then the second highest indicator also includes the body unit, namely shoes. Meanwhile, the hair indicator is the third highest discussed. Apart from that, the discussion that is rarely discussed is about the face and body. Shows that members of the Blue Blood denim community are quite sensitive to the act of grooming, but by carrying out the act of grooming a sense of self-confidence increases, but they still show an expression of masculinity through what they wear, such as denim pants and boots.